2023
DOI: 10.1021/acssuschemeng.2c06731
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Fabrication of High-Performing Single-Crystal SiC Nanowire Sponges Using Natural Loofah

Abstract: This study presents large-scale fabrication of singlecrystal SiC nanowire (SiC nw ) sponges through a carbothermal reduction approach using agricultural residue loofah, which is believed to be a perfect alternative to traditional petrochemical materials as the carbon source in industrial fabrication of SiC nanowires, without additional chemical C sources or catalysts. The single-crystal ultralong SiC nw are observed to have diverse morphologies with diameters of 50−400 nm, which possess a significant anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…The formation of SiC NWs can be divided into four processes: SiO gas formation, CO gas formation, nucleation of SiC, and growth of SiC. 72,73 The SiO gas is generated as per the following reactions expressed in eqn (5) and (6):SiO 2 (solid) + C(solid) = SiO(vapor) + CO(vapor)SiO 2 (solid) + Si(solid) = 2SiO(vapor)…”
Section: Resultsmentioning
confidence: 99%
“…The formation of SiC NWs can be divided into four processes: SiO gas formation, CO gas formation, nucleation of SiC, and growth of SiC. 72,73 The SiO gas is generated as per the following reactions expressed in eqn (5) and (6):SiO 2 (solid) + C(solid) = SiO(vapor) + CO(vapor)SiO 2 (solid) + Si(solid) = 2SiO(vapor)…”
Section: Resultsmentioning
confidence: 99%
“…The formation of solid SiC@SiO 2 NWs occurs via gas–gas reactions between the intermediate gases of SiO and CO (as shown in Table S1). The unavoidable presence of trace amounts of O 2 in the equipment, so in the Si–C–O systems, SiO gas should first be formed through possible solid–solid reactions or solid–gas reactions as follows: , 2 S i false( normals false) + O 2 ( g ) = 2 S i O false( normalg false) normalS normali normalO 2 ( s ) + normalC ( s ) = normalS normali normalO ( g ) + normalC normalO ( g ) normalS normali normalO 2 ( s ) + normalC normalO ( g ) = normalS normali normalO ( g ) + normalC normalO 2 ( g ) normalS normali normalO 2 ...…”
Section: Resultsmentioning
confidence: 99%
“…However, Hao et al suggested that reactions and have positive feedback characteristics to each other, so that reaction occurs and leads to stable growth of NWs . The Δ G of reaction is much less than zero in the range of 500–1600 °C, which means that reaction can occur at the synthesis temperature, thus generating a mixture of products that produce SiC crystals and SiO 2 amorphous crystals . As the melting point of SiC is much higher than that of SiO 2 , SiC crystals precipitate and separate out to form SiC@SiO 2 core–shells. , According to the principle of minimum energy, SiC NWs grow along the direction of [111]. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations